Utilizing ultrasound for the extraction of polysaccharides from the tuber of Typhonium giganteum Engl.: Extraction conditions, structural characterization and bioactivities - Xi Peng; Jing-Ya Wang; Kui-Xu Gao; Zhi-Kun Wang; Qiao-Ling Deng; Yao Wang; Mei-Bian Hu; Yu-Jie Liu (Ultrasonics Sonochemistry)
Polysaccharides from the dried tuber of Typhonium giganteum Engl. (TGEPs) were obtained by utilizing ultrasonic-assisted extraction (UAE) as the extraction method. The determination of optimal process parameters for the UAE of TGEPs (TGEP-U) was accomplished through the application of response surface methodology (RSM). The structural characteristics, antioxidant and hypoglycemic effects of TGEP-U and TGEPs obtained by hot water extraction (TGEP-H) were then compared. Consequently, the optimum extraction conditions predicted by RSM for TGEP-U were obtained as adding water at a ratio of 31 mL/g and extracted for 32 min under an ultrasound power of 440 W. In the verification experiment, the actual yield of TGEP-U was 7.32 ± 0.18 %. It was found that UAE could increase the yield and the total sugar content of TGEPs. Meanwhile, chemical composition analysis showed that both TGEP-U and TGEP-H were mainly composed of mannose, rhamnose, glucuronic acid, galacturonic acid, glucose, galactose, arabinose, and fucose, but the monosaccharide molar ratios were changed by UAE. Analysis of molecular weight (Mw) revealed the presence of three primary constituents within TGEP-U, and four main components in TGEP-H, and UAE reduced the average Mw of TGEPs. No obvious difference was found in the Fourier transform infrared spectroscopy analysis of TGEP-U and TGEP-H. The Congo red and Circular dichroism tests demonstrated that TGEP-U and TGEP-H had non-three helical structure. Scanning electron microscope observation further revealed that the aggregation of functional groups within TGEPs may be influenced by ultrasound, thereby affecting their powder morphology. TGEP-U has slightly poorer thermal stability than TGEP-H, which may be affected by ultrasonic cavitation effects. The results also indicated that TGEP-U had better antioxidant and hypoglycemic activity than TGEP-H. In summary, UAE is an effective method to extract and enhance the activity of TGEPs with enormous research value and potentials.